Inequality and Liberal Democracy: A Critical Take on Economic and Political Power Aspects - Preston, Paschal (Javnost-The Public, 2016)
After decades of benign neglect, the issues of economic and social inequalities have re-entered the stage of mainstream political attention and debate in the western heartlands of the capitalist system over the past couple of years. On the face of it, this is no accident or surprise. The renewed attention on economic and social inequality unfolds against a background of very slow, partial and highly uneven “recovery” from a major financial crash which emerged in the north-Atlantic core in 2007–2008. In this setting we observe that the growing attention to issues of inequality in recent times is not unrelated to the manifest amplification of the longer-term trend towards increased economic inequalities that has become more evident in the period since 2008. This article will draw on (engage with) recent work and debates in neighbouring academic fields (political economy, economic sociology, political studies) concerning the sources, meaning and implications of growing economic inequalities. It pays particular attention to the high-profile work of Thomas Piketty on inequality trends. The article will consider the implications of such research and inequality trends for what now passes as liberal economic and political theory and also for the study, forms, conceptualisations and practice of political communication.